Peranan Moral Quontient Suku Dayak dalam Upaya Pemenuhan Kebutuhan Pokok - M Mardawani; Dessy Triana Relita (Sosio-Didaktika: Social Science Education Journal, 2016)
Abstract :This article was written to provide an illustration of how the role of moral quotient in Dayak society in order to fulfill basic needs in Bukit Segaloh Village, Kayan Hilir Subdistrict, Sintang Regency, West Kalimantan. Data collection in this research, researcher did the data collection with descriptive qualitative method by interview, observation, documentation and library research. Dayak Society kept the tradition/ ancestral beliefs in life. In an effort to meet the basic needs of the Dayak society embodied the values  of the so-called moral intelligence (moral quotient). Moral quotient on the Dayak Society in the Bukit Segaloh village can be seen in order to fulfill basic needs of families through livelihood , the marketing system of agricultural / plantation , and forest products as well as activities in other social communities. Dayak Society’s economic system is essentially still in traditional, that is relies in natures.Abstrak : Artikel ini ditulis untuk memberikan gambaran mengenai bagaimana peranan moral quontientSuku Dayak dalam upaya pemenuhan kebutuhan pokok di Desa Bukit Segaloh Kecamatan Kayan Hilir Kabupaten Sintang Kalimantan Barat. Untuk memperoleh data pada penelitian ini, peneliti melakukan pengumpulan data dengan pendekatan kualitatif deskriptif melalui teknik wawancara, observasi, studi dokumentasi dan studi kepustakaan. Masyarakat Suku Dayak memegang teguh adat istiadat/kepercayaan leluhur dalam kehidupannya. Dalam upaya memenuhi kebutuhan pokok pada masyarakat Suku Dayak terkandung nilai-nilai yang disebut kecerdasan moral (moral quontient). Moral quontient Suku Dayak di Desa Bukit Segaloh tampak pada upaya pemenuhan kebutuhan pokok keluarga melalui mata pencaharian, sistem pemasaran hasil pertanian / perkekebunan, dan hasil hutan serta aktivitas dalam komunitas sosial masyarakat lainnya. Sistem perekonomian pada Suku Dayak pada hakikatnya masih bersifat tradisional yakni bergantung pada alamPengutipan: Mardawani., Relita, D. T. (2016). Peranan Moral  Quontient Suku Dayak dalam Upaya Pemenuhan Kebutuhan Pokok. SOSIO DIDAKTIKA: Social Science Education Journal, 3(1), 2016, 62-69. doi:10.15408/sd.v3i1.3798.Permalink/DOI: http://dx.doi.org/10.15408/sd.v3i1.3798